Pengaruh Kendaraan Berat Terhadap Kinera Ruas Jalan Daengta Qalia Salodong, Kota Makassar - Yudhi (Universitas Kristen Indonesia Paulus, 2025)
Roads are the primary infrastructure playing a crucial role in the smooth flow of land transportation. The design life of a road is the period in years, calculated from the time the road is opened to traffic until major repairs are required or a new surface layer is deemed necessary. The Daengta Qalia Axis serves as an access road connecting several warehouses and factories that will transport logistics using heavy vehicles via Jalan Ir. Sutami, which will be distributed to and from the city of Makassar. The purpose of this research is to determine the influence of the proportion of heavy vehicles on the performance of the Daengta Qalia Salodong road section. The Indonesian Highway Capacity Manual (PKJI) 2023 is used as a guideline. Traffic flow and speed counts were conducted for 1 week. The largest proportion of heavy vehicles, 30.49%, resulted in a degree of saturation of 0.259, however, the average space mean speed was 4.102 km/hour. The high number of heavy vehicles on the 2/2UD section causes smaller vehicles to adjust their speed to that of the heavy vehicles.